2016
DOI: 10.1021/acs.biomac.5b01758
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-Linked Amphiphilic Polymer-Docetaxel Conjugates Assembled Redox-Sensitive Micelles for Efficient Antitumor Drug Delivery

Abstract: Here, we prepared novel redox-sensitive drug delivery system based on copolymer-drug conjugates methoxy poly(ethylene glycol)-poly(γ-benzyl l-glutamate)-disulfide-docetaxel (mPEG-PBLG-SS-DTX) to realize the desirable cancer therapy. First, copolymers of methoxy poly(ethylene glycol)-poly(γ-benzyl l-glutamate) (mPEG-PBLGs) with different molecular weight (mPEG2000-PBLG1750 and mPEG5000-PBLG1750) were synthesized via the ring open polymerization (ROP) of 5-benzyl-l-glutamate-N-carboxyanhydride (γ-Bzl-l-Glu-NCA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 54 publications
3
68
0
Order By: Relevance
“…Furthermore, the micelle concentration of the kick point was defined as the CMC. As evident from the data shown in Figure , the CMC of the mixed micelles was 5.08 μg mL −1 , which was analogous to that of the PEG–PBLG‐SS‐DTX micelles . The relatively low CMC might guarantee stability of the mixed micelles after intravenous administration and dilution in the circulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the micelle concentration of the kick point was defined as the CMC. As evident from the data shown in Figure , the CMC of the mixed micelles was 5.08 μg mL −1 , which was analogous to that of the PEG–PBLG‐SS‐DTX micelles . The relatively low CMC might guarantee stability of the mixed micelles after intravenous administration and dilution in the circulation.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we constructed a multifunctional drug delivery system combining redox sensitivity and tumor‐targeting capacity based on our synthesized redox‐sensitive polymer–drug conjugate methoxy poly(ethylene glycol)–poly(γ‐benzyl l ‐glutamate)‐disulfide‐docetaxel (PEG 2000 –PBLG 1750 ‐SS‐DTX) and active‐targeting polymer PEG–FA. As revealed in Scheme , the redox‐sensitive PEG–PBLG‐SS‐DTX copolymer and tumor‐targeted PEG–FA self‐assembled into multi‐functional mixed micelles in an aqueous environment, which tended to accumulate in tumor tissues due to the EPR effect after intravenous injection.…”
Section: Introductionmentioning
confidence: 99%
“…Other anticancer drugs, such as cisplatin, PTX (Zhang, Zhang, et al, ) and tioguanine (van der Vlies, Hasegawa, & Hubbell, ) have also been utilized to conjugate to the polymers for preparation of BCPs via disulfide bonds, all of which could self‐assemble into micellar nanoparticles for in vivo delivery. Disulfide bonds provided the possibility for controlled release inside targeting tumor cells.…”
Section: Reduction‐responsive Linkage In Bcpsmentioning
confidence: 99%
“…In 2016, Zhang et al [37] reported the synthesis of a novel redox-sensitive drug delivery system based on poly(ethylene glycol)-b-poly(γ-benzyl L-glutamate)-SS-docetaxel (mPEG-b-PBLG-SS-DTX) conjugates. Copolymers of methoxy poly(ethylene glycol)-b-poly(γ-benzyl L-glutamate) (mPEG-PBLGs) with different molecular weights were synthesized via the ROP of BLG-NCA initiated by mPEG-NH 2 .…”
Section: Redox-responsive Micellesmentioning
confidence: 99%